Crotoxin, a rattlesnake toxin, down-modulates functions of bone marrow neutrophils and impairs the Syk-GTPase pathway. (15th September 2017) - Lima, Tatiane S.; Neves, Camila L.; Zambelli, Vanessa O.; Lopes, Flávia S.R.; Sampaio, Sandra C.; Cirillo, Maria Cristina
Abstract: Neutrophils have a critical role in the innate immune response; these cells represent the primary line of defense against invading pathogens or tissue injury. Crotoxin (CTX), the major toxin of the South American rattlesnake ( Crotalus durissus terrificus ) venom, presents longstanding anti-inflammatory properties, inhibiting neutrophil migration and phagocytosis by peritoneal neutrophils for 14 days. Herein, to elucidate these sustained inhibitory effects induced by CTX, we performed in vitro and in vivo studies evaluating the functionality of bone marrow neutrophils and possible molecular mechanisms associated with these effects. CTX inhibited the processes of chemotaxis, adhesion to fibronectin, and phagocytosis of opsonized particles; however, it did not affect ROS production or degranulation in bone marrow neutrophils. To understand the molecular mechanisms that orchestrate this effect, we investigated the expression of CR3 on the neutrophil surface and the total expression and activity of signaling proteins from the Syk-GTPase pathway, which is involved in actin polymerization. CTX down-regulated both subunits of CR3, as well as, the activity of Syk, Vav1, Cdc42, Rac1 and RhoA, and the expression of the subunit 1B from Arp2/3. Together, our findings demonstrated that CTX inhibits the functionally of bone marrow neutrophils and that this effect may be associated with an impairment of the Syk-GTPase pathway. This study demonstrates, for the first time, that the sustained down-modulatory effect of CTX on circulating and peritoneal neutrophils is associated with functional modifications of neutrophils still in the bone marrow, and it also contributes to a better understanding of the anti-inflammatory effect of CTX. Highlights: Crotoxin down-modulates functions of bone marrow neutrophils. The mechanism relies on inhibition of the Syk-GTPase pathway. The sustained anti-inflammatory effect depends on modulation of bone-marrow cells.